Nationalistic Media Obsession With Olympic Medal Counts: The Case of the 2020 Tokyo Olympic Games - Dittmore, Steve; Kim, Kibaek (Frontiers in Sports and Active Living, 2022)
Because Olympic medals are awarded to athletes representing an individual National Olympic Committee, it is natural for the media, and even the International Olympic Committee, to create a table indicating which nation has experienced the most athletic success. Problems, and even disagreements, arise when nations utilize different methods to count medals. The 2020 Tokyo Olympic Games, contested in 2021, provided a unique opportunity to observe how media organizations create a narrative around medal tables. American media outlets preferred to consistently show the United States at the top of the medal standings even though China had more gold medals for much of the Games’ fortnight. Non-American media organizations took exception to that method of counting.